Prevalence of Temporomandibular Dysfunction in Patients with Dentures and Association with Psychological Factors (Research, Society and Development, 2021)
The term TMD is used to define conditions involving changes in the structure and / or function of the masticatory system involving temporomandibular joint (TMJ) and related musculoskeletal structures. Despite the development of Preventive Dentistry during the last decades and the advent of integrated bone implants, it is still possible to find individuals who require rehabilitation with a conventional full denture. Regardless of the cause of edentulism, TMD can affect total edentulous patients, with or without dentures. Inexplicably, the edentulous individuals have not been considered for a long time, and still, in the present context, the scientific publications with significant relevance, referring to the prevalence of TMD in total edentulous individuals, with or without total dentures, are still scarce and controversial, providing no basis for a consistent and reliable conclusion. Type of study: cross-sectional study. Methods: Fifty patients with total dentures were evaluated. The individuals were grouped according to the clinical and psychological diagnosis through RDC / TMD. It was carried out retention and stability test and vertical dimension. Results: The presence of TMD was found in only 14% of the sample. 86% of patients reported stability and poor retention, normal DVO with normal in 70% patients and 62% of patients were diagnosed with moderate depression. Conclusion: In the present study, the TMD obtained a low percentage in the sample. There was a significant association between the presence of TMD and the degree of depression.